Hepatic compression due to a voluminous right kidney tumor - Davidenko, Nicolás; Casanova de Davidenko, Marys; Silva García, Ernesto; Davidenko, Antonio (Cirugía del Uruguay, 1979)
A patient suffered from compression of liver caused by a voluminous right renal growth, resulting in almost complete atrophy of right lobe and compensatcry hypertrophy of left lobe. Oleohepatography made diagnosis possible in preoperatory stage thanks to excretion urography produced concomitantly in said study; this is of great value in diagnosis far establishing difference between intrahepatic and renal expansive processes. No similar case was found in bibliography.